JoJo and Daddy bake a cake - O'Connor, Jane; Preiss-Glasser, Robin; Whipple, Rick (New York, NY Harper, an imprint of HarperCollinsPublishers, 2017)
JoJo and Daddy bake a cake for a surprise recipient
"Pictures based on the art of Robin Preiss Glasser." -- Cover
Guided reading level: F
Ages 4-8
2
Keywords: Cake -- Juvenile fiction; Cake; Families -- Juvenile fiction; Families; Fathers and daughters -- Juvenile fiction; Fathers and daughters; JUVENILE FICTION / Cooking & Food; JUVENILE FICTION / Family / Siblings; JUVENILE FICTION / Reader - Beginner; Cake -- Fiction; Family life -- Fiction; Fathers and daughters -- Fiction; Fiction; Juvenile works; Readers (Publications); Readers (Publications); Early Reader